1961
DOI: 10.1530/jrf.0.0020080
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Fertility of Mice With Orthotopic Ovarian Grafts

Abstract: X-irradiation and received orthotopic grafts ofovarian tissue from donors of the same strain. A linear relationship was demonstrated between log. age and the number of oocytes in both normal ovaries and orthotopically grafted ovarian tissue of G strain (CBA/Fa-a*) mice. It was calculated from the regressions that an average of 65% of the oocytes in the implanted tissue was lost within a few days of grafting. However, the subsequent rate of oocyte loss was reduced so that the potential reproductive life of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This, however, introduces another hazard the homograft reaction which may have a considerable yet variable effect upon the establishment of intrastrain orthotopic grafts and the fertility of recipients (Parrott & Parkes, 1959). Even when inbred strains of mice were used, grafting resulted in great loss of oocytes which shortened the reproductive life of graft recipients to about half of the normal span (Mussett & Parrott, 1961). More¬ over, the average size of litters born to mice with orthotopic ovarian grafts was small and pseudopregnancies and resorbed pregnancies were more frequent than in normal mice of the same age (Mussett & Parrott, 1961).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, introduces another hazard the homograft reaction which may have a considerable yet variable effect upon the establishment of intrastrain orthotopic grafts and the fertility of recipients (Parrott & Parkes, 1959). Even when inbred strains of mice were used, grafting resulted in great loss of oocytes which shortened the reproductive life of graft recipients to about half of the normal span (Mussett & Parrott, 1961). More¬ over, the average size of litters born to mice with orthotopic ovarian grafts was small and pseudopregnancies and resorbed pregnancies were more frequent than in normal mice of the same age (Mussett & Parrott, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Even when inbred strains of mice were used, grafting resulted in great loss of oocytes which shortened the reproductive life of graft recipients to about half of the normal span (Mussett & Parrott, 1961). More¬ over, the average size of litters born to mice with orthotopic ovarian grafts was small and pseudopregnancies and resorbed pregnancies were more frequent than in normal mice of the same age (Mussett & Parrott, 1961). In consequence, all the results obtained from mice with grafts of frozen tissue have been com¬ pared with results from other mice of the same strain and age which had received grafts of freshly donated ovarian tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that ovarian tissue grafting, even without cryopreservation, induces a dramatic follicular loss (Mussett & Parrott 1961, Newton et al 1996, Nisolle et al 2000, Shaw et al 2000, Borges et al 2009), irrespective of grafting site (Wang et al 2002), the age of donors and recipients , and even species (Salle et al 2003, Gook et al 2005. This is associated with a reduced graft size and significant fibrosis in most grafts (Agca et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that ovarian grafting, even without cryopreservation [62], induces a dramatic follicular loss (65%), whatever the age of donors and recipients (adult-adult or pre pubertal-adults [22]) or the location of graft (orthotopic or under kidney capsule [63]). This has also been reported in sheep [64] and in few cases of re-implanted cryopreserved human ovaries [65].…”
Section: Discussionmentioning
confidence: 99%